Unions and workers' well-being - Laszlo Goerke (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2020)
If individuals join a trade union their utility should increase. Therefore, union members can be expected to exhibit higher job satisfaction than comparable non-members. This expectation is not consistent with empirical findings. The evidence sometimes indicates that union members have lower job satisfaction, but overall suggests the absence of a robust correlation. This survey discusses empirically relevant determinants of the relationship between trade union membership and job satisfaction. It distinguishes settings in which a trade union provides public goods from those in which it restricts the provision of benefits to its members. Furthermore, the survey summarizes the empirical evidence and indicates possible future research issues.
Keywords: I31; J28; J51; J52; 330; Collective Bargaining Coverage; Job Satisfaction; Life Satisfaction; Trade Union Membership